OM-MSCs Alleviate the Golgi Apparatus Stress Response following Cerebral Ischemia/Reperfusion Injury via the PEDF-PI3K/Akt/mTOR Signaling Pathway - Jialin He (Hindawi Limited, 2021)
The mechanism of Golgi apparatus (GA) stress responses mediated by GOLPH3 has been widely studied in ischemic stroke, and the neuroprotection effect of olfactory mucosa mesenchymal stem cells (OM-MSCs) against cerebral ischemia/reperfusion injury (IRI) has been preliminarily presented. However, the exact role of OM-MSCs in the GA stress response following cerebral IRI remains to be elucidated. In the present study, we used an oxygen-glucose deprivation/reoxygenation (OGD/R) model and reversible middle cerebral artery occlusion (MCAO) model to simulate cerebral IRI in vitro and in vivo. Our results showed that the level of GOLPH3 protein, reactive oxygen species (ROS), and Ca2+ was upregulated, SPCA1 level was downregulated, and GA fragmentation was increased in ischemic stroke models, and OM-MSC treatment clearly ameliorated these GA stress responses in vitro and in vivo. Subsequently, the knockdown of PEDF in OM-MSCs using PEDF-specific siRNA further demonstrated that secretion of PEDF in OM-MSCs protected OGD/R-treated N2a cells and MCAO rats from GA stress response. Additionally, rescue experiment using specific pathway inhibitors suggested that OM-MSCs could promote the phosphorylation of the PI3K/Akt/mTOR pathway, thereby mitigating OGD/R-induced GA stress response and excessive autophagy. In conclusion, OM-MSCs minimized the GA stress response following cerebral IRI, at least partially, through the PEDF-PI3K/Akt/mTOR pathway.